Сравнительная оценка нейропротективного действия производных L-лизина в условиях острой алкогольной интоксикации - Беленичев, И. Ф.; Павлюк, И. В.; Кучеренко, Л. И.; Belienichev, I. F.; Pavliuk, I. V.; Kucherenko, L. I.; Бєленічев, Ігор Федорович; Кучеренко, Людмила Іванівна (Полтава : Укр. мед. стомат. акад., 2016)
Резюме. Моделирование тяжелой формы острой интоксикации этанолом, вызванной однократным его введением в дозе 0,8ЛД50 перорально, приводит у животных контрольной группы (белые беспородные крысы самцы массой 160-180) к тяжелым неврологическим нарушениям. В головном мозге животных контрольной группы отмечали увеличение маркеров оксидативного стресса — АФГ и КФГ и нитрозирующего стресса — нитротирозина. Производные L-лизина — Ангиолин (50 мг/кг), L-лизина гидрохлорид (100 мг/кг), L-лизина эссцинат (0,5 мл/кг), N6-(1-иминоэтил) -L-лизина дигидрохлорид (20 мг/кг), а также референс-препарат Милдронат (100 мг/кг) вводили внутрибрюшинно через 30 мин. после алкоголизации. Все изучаемые производные L-лизина оказывают, в разной степени выраженности и с разным латентным периодом, нейропротективное действие, которое направлено на уменьшение неврологических нарушений, восстановление поведенческих реакций и на снижение оксидативной нейродеструкции. Наиболее активным среди всех изучаемых производных L-лизина является Ангиолин, что является экспериментальным обоснованием для его углубленного изучения. Резюме. Моделювання важкої форми гострої інтоксикації етанолом, викликаної одноразовим його введенням в дозі 0,8ЛД50 перорально, призводить у тварин контрольної групи (білі безпородні щури самці масою 160-180) до важких неврологічних порушень. У головному мозку тварин контрольної групи відзначали збільшення маркерів оксидативного стресу — АФГ і КФГ і нітрозируючого стресу — нітротирозину. Похідні L-лізину — Ангіоліна (50 мг/кг), L-лізину гідрохлорид (100 мг/кг), L-лізину ессцінат (0,5 мл/кг), N6- (1-іміноетіл) -L-лізину дигідрохлорид (20 мг/кг), а також референс-препарат Мілдронат (100 мг/кг) вводили внутрішньочеревинно через 30 хв. після алкоголізації. Всі досліджувані похідні L-лізину чинять, з різним ступенем вираженості і з різним латентним періодом, нейропротективну дію, яка спрямована на зменшення неврологічних порушень, відновлення поведінкових реакцій і на зниження оксидативної нейродеструкції. Найбільш активним серед всіх досліджуваних похідних L-лізину є Ангіолін, що є експериментальним обгрунтуванням для його поглибленого вивчення. Abstract. The development of new neuroprotective methods pertaining alcoholism becomes relevant objective of the present stage pharmacology. The comparative evaluation of derivatives neuroprotective effect of L-lysine — L-lysine hydrochloride, L-lysine escinate, (S)-2,6 diaminohexanoic acid 3-methyl-1,2,4-triazolyl-5-thioacetate (Angiolin) and N6-(1-iminoethyl) -L-lysine dihydrochloride in modeling of acute alcohol intoxication was carried out. The research was performed on 70 white outbred male rats weighing 160-180 grams. The model of acute severe alcohol intoxication (AAI) was provided by single dosing intragastric administration of 25% ethanol solution in amount of 22.4 g/kg. Used ethanol amount is considered the dose of high toxicity (its value is 0.8LD50). The investigational drugs were administered to animals 30 minutes after the alcohol introduction intraperitoneally single dosing: angiolin ((S)-2.6 diaminohexanoic acid 3-methyl-1,2,4-triazolyl-5-thioacetate) (SPA «Pharmatron», Ukraine) dosing 50 mg/kg, L-lysine hydrochloride (Sigma, USA) − 100 mg/kg, L-lysine aescinat (Corporation «Arterium», Ukraine) − 0,5 ml/kg), N6-(1-iminoethyl) -L-lysine dihydrochloride, (Tocris Bioscience, UK) − 20 mg/kg. Mildronate (100 mg/kg) was administered as the reference drug. The index of neurological disorders severity was calculated to assess the depression degree of CNS functioning under ethanol effect. The experimental animals condition that corresponded to degree of acute alcohol human intoxication was represented in points by the mentioned index. In 3 days after alcoholization animals were removed from the experiment (thiopental sodium, 40 mg/kg) and concentration of oxidative stress markers – aldehyde phenylhydrazones (APH), carboxy phenylhydrazones (CPH) and nitrosating stress markers concentration − nitrotyrosine was determined in the brain. Comparison of the groups was carried out using the criterion Whitney-Mann U-test. Modeling of acute alcohol intoxication (control) caused severe neurological disorders: the gag reflex, flexion reflex of the hind limbs, pupillary reflex, corneal reflex were depressed in animals, both the tactile-pain sensitivity and behavioral responses were inhibited, that is the animals did not react when were taken in arms, did not respond to sound stimuli, did not roll over, could not move by themselves. The significant increase of APH, CPH and nitrotyrosine was recorded in the brain of the animals in 3 days after alcoholization that indicated the oxidative neurodestruction. The results of the research stated that all studied L-lysine derivatives have neuroprotective effect, in varying intensity and different latent period (increase of the neurological disorders severity index, reduction of nitrosating and oxidative stress markers) under conditions of acute alcohol intoxication. The protective effect of L-lysine derivatives on the brain is aimed at neurological disorders reducing, recovery of the behavioral reactions (the animals responded to sound stimuli more rapidly and also when were taken in arms, rolled over, began to move by themselves) as well as the reduction of oxidative neurodestructive markers − APH, CPH and nitrotyrosine. The neuroprotective effect of two derivatives of L-lysine — Angiolin and N6-(1-iminoethyl)-L-lysine dihydrochloride significantly exceeds the effectiveness of Mildronate and two derivatives — L-lysine aescinat and L-lysine hydrochloride are comparable to it. The most active among all studied derivatives of L-lysine is Angiolin, which has the most pronounced effect and the most early reliable neuroprotective effect according to registration time. The obtained results are the experimental validation for further profound study of the neuroprotective Angiolin effect and its dosage forms in chronical alcohol intoxication.
Порівняльна оцінка нейропротективної дії похідних L-лізину в умовах гострої алкогольної інтоксикації
Comparative evaluation of the neuroprotective effect of l-lysine derivatives under acute alcohol intoxication
Keywords: острая алкогольная интоксикация; нейропротекция; Ангиолин; L-лизина гидрохлорид; L-лизина эссцинат; N6-(1-иминоэтил) -L-лизина дигидрохлорид; Милдронат; гостра алкогольна інтоксикація; нейропротекція; Ангіолін; L-лізину гідрохлорид; L-лізину ессцінат; N6- (1-іміноетіл) -L-лізину дигідрохлорид; Мілдронат; acute alcohol intoxication; neuroprotection; Angiolin; L-lysine hydrochloride; L-lysine aescinat; N6- (1-iminoethyl) -L-lysine dihydrochloride; Mildronat